2009
DOI: 10.1002/ajpa.21063
|View full text |Cite
|
Sign up to set email alerts
|

Habitual throwing and swimming correspond with upper limb diaphyseal strength and shape in modern human athletes

Abstract: Variation in upper limb long bone cross-sectional properties may reflect a phenotypically plastic response to habitual loading patterns. Structural differences between limb bones have often been used to infer past behavior from hominin remains; however, few studies have examined direct relationships between behavioral differences and bone structure in humans. To help address this, cross-sectional images (50% length) of the humeri and ulnae of university varsity-level swimmers, cricketers, and controls were cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 63 publications
7
188
1
3
Order By: Relevance
“…S2). These adaptation data exceed previous reports of upper extremity bilateral asymmetry induced by physical activity (12,13,20,22,(33)(34)(35), establishing new levels for the plastic potential within the skeleton. Similar magnitudes of bilateral asymmetry are not expected in studies of the lower extremity because of the heightened habitual bilateral loading associated with weight-bearing in both athletes and controls.…”
Section: Discussioncontrasting
confidence: 89%
“…S2). These adaptation data exceed previous reports of upper extremity bilateral asymmetry induced by physical activity (12,13,20,22,(33)(34)(35), establishing new levels for the plastic potential within the skeleton. Similar magnitudes of bilateral asymmetry are not expected in studies of the lower extremity because of the heightened habitual bilateral loading associated with weight-bearing in both athletes and controls.…”
Section: Discussioncontrasting
confidence: 89%
“…However a recent examination on habitual throwing and swimming upon diaphyseal strength of upper limbs in cricketers and swimmers revealed that greater mechanical loads placed upon upper limbs, whether unilaterally or bilaterally, resulted in greater strength compared to less mechanical load (non-dominant limb or controls) (Shaw & Stock, 2009). This finding demonstrates how repetitive activity or sport may lead to asymmetries within the body, however, whether this finding translates to the lower limbs is unknown.…”
Section: Geometric/anthropometricmentioning
confidence: 99%
“…For example, tennis and baseball players, in addition to cricketers, exhibit bilateral asymmetry in some indices of forelimb robusticity (Jones et al 1977;Shaw and Stock 2009;Warden et al 2009), and rowers have more robust humeri than nonrowers (Weiss 2003). Such associations have allowed researchers to infer habitual use of watercraft among populations who exploit aquatic resources (Stock and Pfeiffer 2001) or habitual digging with sticks by Late Stone Age foragers (Stock and Pfeiffer 2004).…”
mentioning
confidence: 99%